Urgensi Pengaturan Femisida Sebagai Tindak Pidana Dalam Hukum Pidana Nasional Indonesia - Feronika BR Simamora, Elisa; Sudarti, Elly; Rakhmawati, Dessy (PAMPAS: Journal of Criminal Law, 2026)
This research aims to find out and analyze the regulation of femicide in the current Indonesian national criminal law system, as well as examine the direction of Indonesia's criminal law policy towards femicide in the future. The problems analyzed include how femicide is regulated in the current Indonesian national criminal law system, as well as how criminal law policies should be carried out against femicide as a criminal act in the criminal law system in Indonesia in the future. The research method used is normative juridical with conceptual, legislative, case, and comparative approaches, especially with Brazil and Mexico which have comprehensively regulated femicide. The results of the study show that Indonesia's criminal law, including the Criminal Code and Law Number 12 of 2022 concerning the Crime of Sexual Violence, has not been able to identify femicide as gender-based murder. Law enforcement is still partial, focusing on the element of murder Law enforcement is still partial, focusing on the element of murder without paying attention to misogynistic motives and imbalances in power relations between perpetrators and victims. Comparative studies show that Brazil and Mexico have succeeded in strengthening victim protection, improving the accuracy of data collection, and improving investigation and prosecution mechanisms through special arrangements on femicide. The conclusion of this study emphasizes the importance of the formation of a special femicide-specific offense or the application of a hybrid model in the Indonesian criminal law system. These reforms are needed to realize more comprehensive, gender- sensitive, and equitable legal protections for women as a vulnerable group to gender-based killings. ABSTRAK Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaturan femisida dalam sistem hukum pidana nasional Indonesia saat ini, serta mengkaji arah kebijakan hukum pidana Indonesia terhadap femisida di masa mendatang. Permasalahan yang dianalisis meliputi bagaimana pengaturan femisida dalam sistem hukum pidana nasional Indonesia saat ini, serta bagaimana kebijakan hukum pidana seharusnya dilakukan terhadap femisida sebagai tindak pidana dalam sistem hukum pidana di Indonesia kedepan. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan konseptual, perundang-undangan, kasus, dan perbandingan khususnya dengan Brasil dan Meksiko yang telah mengatur femisida secara komprehensif. Hasil penelitian menunjukkan bahwa hukum pidana Indonesia, termasuk Kitab Undang-undang Hukum Pidana dan UU Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual, belum mampu mengidentifikasi femisida sebagai pembunuhan berbasis gender. Penegakan hukum masih bersifat parsial, berfokus pada unsur pembunuhan tanpa memperhatikan motif misoginis dan ketimpangan relasi kuasa antara pelaku dan korban. Studi perbandingan menunjukkan bahwa Brasil dan Meksiko berhasil memperkuat perlindungan korban, meningkatkan akurasi pendataan, serta memperbaiki mekanisme penyidikan dan penuntutan melalui pengaturan khusus tentang feminicidio. Kesimpulan penelitian ini menegaskan pentingnya pembentukan delik khusus femisida atau penerapan model hybrid dalam sistem hukum pidana Indonesia. Reformasi ini diperlukan untuk mewujudkan perlindungan hukum yang lebih komprehensif, sensitif gender, dan berkeadilan bagi perempuan sebagai kelompok rentan terhadap pembunuhan berbasis gender.